Importancia de la educación física en el desarrollo psicomotriz en estudiantes de básica media de la Escuela Once de Noviembre - Rosales Puma, Lenin Yordani; Romero Atiencie, Famer Oswaldo (Machala: Universidad Técnica de Machala, 2022)
The present research work is an integrative project whose purpose was to analyse the importance of physical education in the psychomotor development of secondary school students at the eleventh grade school in November, whose general objective was to determine the problems that arise in the development of physical education classes and the consequences for the psychomotor skills of secondary school students at the eleventh grade school in november, while the specific objectives were determined as follows, to analyse the type of orientation that the physical education teacher maintains with the students of the intermediate sub-level to improve psychomotor skills, to determine what physical education contributes to the psychomotor development of children in basic secondary education through field research in the november eleventh school and to propose orientations on the curricular blocks in the subject of physical education to contribute to the psychomotor development of students in basic secondary education in the november eleventh. The data collection was based on a qualitative-descriptive approach, with an analytical-synthetic and inductive-deductive methodology of a descriptive nature, achieving a diagnosis of the reality in the eleventh of november school, in terms of the relationship between the objects of study, physical education and psychomotor skills were determined. The methods of greatest incidence in this enquiry are the analytical-synthetic method and others that were integrated as auxiliary methods, such as the comparative and bibliographical methods, which contributed significantly at the time of gathering the information based on the specific objectives to contribute to the general objective, which were written to cover aspects related to the literature review, the field research and finally to support the integrative proposal, as a contribution in favour of the educational institution that facilitated access to carry out the research. In relation to the sample, all the students of the intermediate sub-level were considered; in addition, the teachers of the intermediate sub-level of the eleventh of November school were also taken into account. The instruments selected were the bibliographic manager - mendeley, which for its construction was related to the objects of study, from which two dimensions were derived and consequently the indicators served as a guide for the elaboration of the instruments with a Likert scale, which facilitated the reception of opinions and attitudes of the students involved in this research work, at the same time scoring from fixed answers the range of values. The analysis of the results of the survey showed that classroom teachers do not have adequate knowledge about physical education classes, therefore, and in response to the third specific objective, the integrative proposal was defined, which is aimed at improving physical education classes and psychomotor development. The proposal was composed of three phases aimed at classroom teachers, it also included logistical resources and the assessment of feasibility with the dimensions.
El presente trabajo de investigación se trata de un proyecto integrador, tuvo como propósito, analizar la importancia de la educación física en el desarrollo psicomotriz en estudiantes de básica media de la escuela once de noviembre, cuyo objetivo general se orientó en, determinar los problemas que se presentan en el desarrollo de las clases de educación física y consecuencias en la psicomotricidad de los estudiantes de la educación básica media de la escuela once de noviembre, mientras que en los objetivos específicos se determinó de la siguiente manera, analizar el tipo de orientación que mantiene el docente de educación física con los estudiantes del subnivel medio para mejorar la psicomotricidad; determinar que aporta la educación física en el desarrollo psicomotriz de los niños de educación básica media mediante la investigación de campo en la escuela once de noviembre y proponer orientaciones sobre los bloques curriculares en la asignatura de educación física para contribuir con el desarrollo psicomotriz de los estudiantes de básica media de la escuela once de noviembre. La recopilación de datos se fundamentó desde el enfoque cualitativa – descriptiva, con una metodología analítico – sintético e inductivo – deductivo de carácter descriptivo, logrando diagnosticar la realidad en la escuela once de noviembre, en cuanto a la relación de los objetos de estudio se determinó educación física y psicomotricidad. Los métodos de mayor incidencia en esta indagación es el analítico-sintético y otros que se integraron en calidad de auxiliares, como, el comparativo y el bibliográfico, estos que aportaron significativamente al momento de recabar la información basándonos en los objetivos específicos para contribuir al objetivo general, mismos que estuvieron redactados para abarcar aspectos relacionados con la revisión literaria, con la investigación de campo y finalmente para sostener la propuesta integradora, como aporte a favor de la institución educativa que facilitó el acceso para concretar la investigación. En relación con la muestra se consideró a todos los estudiantes del subnivel medio, además, se tomó en cuenta a los docentes del subnivel medio del plantel educativo once de noviembre. Los instrumentos seleccionados fue el gestor bibliográfico – Mendeley, que para su construcción se relacionó los objetos de estudio, de donde se derivaron dos dimensiones y en consecuencia los indicadores sirvieron de guía para la elaboración de los instrumentos con una escala de Likert, que facilitó la recepción de opiniones y actitudes de los estudiantes involucrados en este trabajo de investigación, al mismo tiempo puntuar a partir de respuestas fijas el rango de valores. El análisis de resultados en la encuesta se demuestra que los docentes de aula no tienen un conocimiento adecuado sobre las clases de educación física, por lo consiguiente y respondiendo al tercer objetivo específico, se definió la propuesta integradora que está orientada a mejorar las clases de educación física y el desarrollo psicomotriz. La propuesta estuvo compuesta de tres fases dirigidas a los docentes de aula, además se incluyó los recursos logísticos y la valoración de la factibilidad con las dimensiones.
Keywords: EDUCACION FISICA; PSICOMOTRICIDAD